PENGELOLAAN SURAT MASUK DENGAN MENGGUNAKAN APLIKASI E-OFFICE VER. 1.0 PT PAL INDONESIA - Ridho Muarief; Sintaria Praptinasari; Ahris Nadhifah (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2022)
Letters are important documents that are definitely needed in a company. Therefore, it is necessary to do good and correct management of letters so that the letters can be well organized and the process of recovering letters can be carried out effectively and efficiently. Along with the development of information technology, mail management is carried out centrally using a system called e-office. PT PAL Indonesia participated in using e-office ver 1.0 to manage the company's internal incoming mail. The purpose of this study is to describe the management of incoming mail using the e-office ver application. 1.0 in the Quality Assurance Division of PT PAL Indonesia. The theoretical basis used is the management of incoming mail according to Dr. Durotul Yatimah. The method used is descriptive qualitative. Sources of data obtained from interviews, observations, and documentation, which are then presented and compared with the theory used. It was found that the management of incoming mail by using the e-office ver application. 1.0 in the Quality Assurance Division of PT PAL Indonesia is in accordance with the indicators in the theory of incoming mail management according to Dr. Durotul Yatimah. In the future, PT PAL Indonesia can create an e-office ver application. 1.0 in mobile form that can be installed on employee cellphones so that notifications of new incoming letters can be read immediately.